Multiple Religious Belonging after Religion: Theorising Strategic Religious Participation in a Shared Religious Landscape as a Chinese Model - Hedges Paul (Open Theology, 2017)
It is argued that the concept of Multiple Religious Belonging as normally conceived relies upon a problematic construction of “religion” which can be expressed as the World Religions Paradigm. This relies upon a modern Western Protestant bias as to how “religion” should be understood. It is argued that religion can be understood otherwise, and looking at the Chinese context an argument is made that participation in different religious traditions relies upon a very different construct from Multiple Religious Belonging via the World Religions Paradigm model. This is termed Strategic Religious Participation in a Shared Religious Landscape. It considers the way that Chinese religiosity does not have fixed borders in the same way as the World Religions Paradigm suggests. Indeed, asking whether there is Multiple Religious Belonging in traditional Chinese thought seems to misconstrue the situation. A final reflection asks whether this new paradigm, of Strategic Religious Participation in a Shared Religious Landscape, may be appropriate to look at the contemporary Western context amongst a number of religious “nones”. Although no definitive answer is given to this question, the issue highlights that the World Religions Paradigm which shapes our sense of Multiple Religious Belonging may need to be rethought within different contexts.